Eco-innovation in the cleaning process: An application of dry ice blasting in automotive painting industry. (1st November 2020) - Onofre, Ana; Godina, Radu; Carvalho, Helena; Catarino, Isabel
Abstract: In the field of the automotive painting industry, the conventional cleaning process uses solvents and high amounts of water to clean different substrates. However, not all solvents are suitable for every type of material, so different types of solvents should be used in order to successfully clean different types of material, as the product under fabrication changes, otherwise, a compromise has to be reached. The current cleaning operation system and respective apparatus occupies a significant area of the industrial facility and uses abundant water. Such use of water requires subsequent drying of the cleaned parts and for residual water treatment, leading to high running costs. In this sense, dry ice blasting appears as an alternative to the current process. This method consists of the projection of solid carbon dioxide particles onto a surface as a means of eliminating stains and contaminants prior to the painting. It is suitable for a wider range of substrates, and the necessary equipment occupies significantly less space when compared with the current process. Thus, there is potential for cost savings. In an industrial painting context, this application is considered new, although its physical principle has been established since the late 1980s. The present study aims to qualitatively evaluate the dry ice blasting process according to the quality standards of an industrial unit. Two types of plastic substrates for automotive parts are tested on-site by using a manual dry ice blasting kit, subject to the normal painting process, and then analyzed according to industrial standards. The results show that the process under study meets all the required quality standards. After being painted, the average number of stains per piece is of the same order of magnitude as the normal production, emphasizing that the average primary stains are lower in the process under study. CO2 emissions and cleaning time is greatly reduced, the cleaning runtime decreased by 96.9% if the dry ice is used as an alternative. The viability of dry ice blasting in the pre-painting of plastic surfaces was demonstrated, and the eco-innovation of the new process discussed. Highlights: Application of dry ice blasting in automotive painting industry. The process under study meets all the required quality standards. Viability of dry ice blasting in pre-painting of plastic surfaces is demonstrated. CO2 emissions and cleaning time is greatly reduced. The cleaning runtime decreased by 96.9% if the dry ice is used.